(untitled) (Research, Society and Development, 2020)
Heavy metal-contaminated areas are a recurring problem in a society that increasingly demands fossil fuels, pesticides and fertilizers. Traditional methods to recover these areas are generally very expensive, and phytoremediation can be a solution for their decontamination by removing these contaminants from the soil through the harvest of the plants grown in the affected site, as these elements are extracted from the soil. The harvested part can be used for non-food purposes, such as energy production. In this scenario, the sorghum plant emerges as an alternative owing to its high ability to accumulate biomass in a short time and bioelectricity production potential. This study proposes to examine the use of biomass sorghum for the bioremediation of environments contaminated with the heavy metals Cu and Ni. The experiment was carried out in the municipality of Jaguariúna - SP, Brazil, using four doses of Ni (0, 10.5, 47 and 210 mg kg-1) and Cu (0, 200, 300 and 400 mg kg-1). The sorghum plants exhibited good development even at the highest Cu and Ni doses applied to the soil. The highest levels of Cu and Ni were concentrated in the roots. Biomass sorghum can be indicated for the phytoremediation of environments contaminated with Cu and Ni.